Prenatal diagnosis of chromosome 18 long arm deletion syndrome by high-throughput sequencing: Two case reports. Issue 50 (17th December 2021) - Bai, Xuechun; Zheng, Lianwen; Ma, Shuai; Kan, Xun
Abstract: Rationale: Chromosome 18 long arm deletion syndrome is a group of clinical syndromes caused by partial or total genetic material deletion of the long arm of chromosome 18 (18q), whose clinical manifestations are related to presentation and developmental abnormalities in various aspects such as intelligence, face, and movement. Prenatal diagnosis of this syndrome is challenging because of its low incidence and uncharacteristic prenatal clinical performance. In this paper, 2 cases of partial deletion of 18q found in prenatal amniotic fluid examination by high-throughput sequencing were reported and analyzed. Patient concerns: In patient 1, non-invasive prenatal gene detection at 21 + 2 weeks of gestation suggests a risk of trisomy 18. In patient 2, ultrasound examination at 21 + 2 weeks of gestation revealed a single live fetus, but it was difficult to pinpoint whether the fetus had only 1 umbilical artery to supply blood. Diagnosis and intervention: The 18q deletion syndrome was diagnosed by chromosome karyotype analysis and high-throughput sequencing. Outcomes: The pregnancies were terminated due to the abnormal chromosome. Lesson: This report adds novel variants to the genetic profile of 18q deletion, in order to enrich the genetic data of long arm deletion of 18 chromosomes and provide better services for pre-screening, diagnosis, and genetic counseling for this disease.